2022
DOI: 10.1371/journal.pone.0267660
|View full text |Cite
|
Sign up to set email alerts
|

Individual and community-level factors associated with skilled birth attendants during delivery in Bangladesh: A multilevel analysis of demographic and health surveys

Abstract: Background Skilled birth attendants (SBAs) play a crucial role in reducing infant and maternal mortality. Although the ratio of skilled assistance at birth has increased in Bangladesh, factors associated with SBA use are unknown. The main goal of our study was to reveal the individual- and community-level factors associated with SBA use during childbirth in Bangladesh. We also showed the prevalence and trend of SBA use and related independent variables in Bangladesh over the past decade. Methods This study u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 61 publications
5
8
0
Order By: Relevance
“…Also medical facilities in urban area are more than rural in Bangladesh; consequently urban mothers are more likely to get SKB than rural mothers. We also observed that comparatively higher educated and rich mothers were more likely to use SKB than their counterparts; these results are supported to the findings of other studies [ 21 , 22 , 24 , 32 ]. Education is an important factor for using SBA during delivery.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Also medical facilities in urban area are more than rural in Bangladesh; consequently urban mothers are more likely to get SKB than rural mothers. We also observed that comparatively higher educated and rich mothers were more likely to use SKB than their counterparts; these results are supported to the findings of other studies [ 21 , 22 , 24 , 32 ]. Education is an important factor for using SBA during delivery.…”
Section: Discussionsupporting
confidence: 91%
“…Same results had been found previous study in Bangladesh [ 22 , 32 ]. We found that more number of urban mothers uses SKB during their delivery than rural mothers, same findings had been found in other studies [ 22 , 24 , 32 ]. Mothers living in urban environment are more educated and living in family having higher wealth quintile than rural are [ 8 ], and educated and rich mothers are more conscious about their health comparatively less educated and poor mothers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Women in their early pregnancies are more likely to use home-based skilled birth attendance compared to later pregnancies. Similar studies also found that with later pregnancies, women are less likely to ask for skilled birth assistance [ 44 , 59 ]. During the first couple of pregnancies women may feel insecure as they don’t have prior experience of child-birth.…”
Section: Discussionmentioning
confidence: 67%
“…Literature showing relationship between BMI and skilled birth attendance is extremely scarce. A study, conducted on women in Bangladesh, found that women whose weight is not normal are more likely to use skilled birth attendance compared to normal-weighted women [ 44 ]. High BMI is associated with a number of health risks such as diabetes, cardiovascular diseases, kidney diseases, stroke etc.…”
Section: Discussionmentioning
confidence: 99%